Unlikely Bridges, Unexpected Circumstances - Heitor Alvelos (Cubic Journal)
This article expounds on the chronology of a PhD programme in design hosted by the University of Porto in cooperation with the University of Aveiro since 2011. Scientific, strategic, pedagogical and administrative occurrences and decisions are narrated and substantiated. Various challenges, as well as approaches for their resolution and/or mitigation, are presented. It is argued that an affective component is crucial to the success of the programme, made possible by the development of immersive research environments and working partnerships between student projects and external contexts (research centres, businesses, cultural agents, multidisciplinarity and internationalisation). A focus on the impact of the COVID-19 pandemic on course management and narratives is presented. It is argued that, in the post-pandemic era, the core challenges now reside in the maintenance of weak ties and affective components towards a stronger sense of community.